A Study on assessing the extent to which market selection and the mode of entry choices contribute to the success of international marketing - Tofiq, Ako Mohammed; Qadir, Aram Mohammed Amin (Technium Social Sciences Journal, 2021)
With every step human take in developing technology, life became easier than before. With every second, technology breaks the borders of countries and make the whole world seems like a small village, a world when you can reach any point in it with a short time and in an easy way. That development in technology has changed every aspect of life, especially for the business world. Technology opened the gates for entrepreneurs who dream of changing the world by remaining in the unit area. In most cases, when a company goes internationally, the dream might become a nightmare, the bubble that mangers imagined burst and all dreams fall. This happens most of the time because of one reason, which is not understanding the market and thinks it will be as the domestic one, and no factor will be added to the process. Knowing about the new market is so important. Still, managers also need to know about the people of that market, because people are different, they are different in interests, in the way they look at something, in the way they get influenced, they are different in almost everything. One of the deepest holes that managers fall into is that they depend on their perspective and ignore that people might not see the product as they see it, they do not analyze that they are different, they have different factors that affect them. The good managers always believe in data, in numbers, not in talking of their employees, customers and owners. That how they can make a good decision that far from risk and false assumptions. Taking a step into the international market could be the first step to the company’s glory and its managers and employees. It could be a step into the hell that will lead to the company name’s disappearance and may the whole company. Due to the importance of that step, it should be studied carefully and know the different elements that are going to do effects, starting from the product itself, market analysis, economic situations and any other small factors, and not ignoring anything even if it was small or weak, because most fail not because of not knowing the small factors, but because not giving recognition to the little factors and thinking that it will not paralyze the company future and operations.